The Cysteine-Containing Cell-Penetrating Peptide AP Enables Efficient Macromolecule Delivery to T Cells and Controls Autoimmune Encephalomyelitis - Won-Ju Kim; Gil-Ran Kim; Hyun-Jung Cho; Je-Min Choi (MDPI AG, 2021)
T cells are key immune cells involved in the pathogenesis of several diseases, rendering them important therapeutic targets. Although drug delivery to T cells is the subject of continuous research, it remains challenging to deliver drugs to primary T cells. Here, we used a peptide-based drug delivery system, AP, which was previously developed as a transdermal delivery peptide, to modulate T cell function. We first identified that AP-conjugated enhanced green fluorescent protein (EGFP) was efficiently delivered to non-phagocytic human T cells. We also confirmed that a nine-amino acid sequence with one cysteine residue was the optimal sequence for protein delivery to T cells. Next, we identified the biodistribution of AP-dTomato protein in vivo after systemic administration, and transduced it to various tissues, such as the spleen, liver, intestines, and even to the brain across the blood-brain barrier. Next, to confirm AP-based T cell regulation, we synthesized the AP-conjugated cytoplasmic domain of CTLA-4, AP-ctCTLA-4 peptide. AP-ctCTLA-4 reduced IL-17A expression under Th17 differentiation conditions in vitro and ameliorated experimental autoimmune encephalomyelitis, with decreased numbers of pathogenic IL-17A+GM-CSF+ CD4 T cells. These results collectively suggest the AP peptide can be used for the successful intracellular regulation of T cell function, especially in the CNS.